2022
DOI: 10.3390/plants11040529
|View full text |Cite
|
Sign up to set email alerts
|

Drying Grapes after the Application of Different Dipping Solutions: Effects on Hormones, Minerals, Vitamins, and Antioxidant Enzymes in Gök Üzüm (Vitis vinifera L.) Raisins

Abstract: (1) Background: Raisins contain a wide range of hormones, minerals, vitamins, and antioxidant enzymes that may contribute to the health benefits of consumers. (2) Methods: The aim of this research was to compare the hormone, mineral, vitamin, and antioxidant capacities of Gök Üzüm (Vitis vinifera L.) raisins immersed in oak ash (OA) and potassium carbonate (PC) dipping solutions before drying. (3) Results: Abscisic acid (ABA) (5751.18–11,868.40 ng g−1) and riboflavin (95.17–135.54 mg 100 g−1) were the most abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…These observations correspond to previous research, affirming the consistency of the results with established patterns in viticulture. As supported by references in the field [6,14], the increase in berry size, rising TSS values, declining acidity, and the improvement in the maturity index are all indicative of the typical ripening process. These parameters serve as crucial indicators for determining the optimal grape harvest time, a fundamental factor in ensuring the production of high-quality wines and grape-based products.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…These observations correspond to previous research, affirming the consistency of the results with established patterns in viticulture. As supported by references in the field [6,14], the increase in berry size, rising TSS values, declining acidity, and the improvement in the maturity index are all indicative of the typical ripening process. These parameters serve as crucial indicators for determining the optimal grape harvest time, a fundamental factor in ensuring the production of high-quality wines and grape-based products.…”
Section: Discussionmentioning
confidence: 53%
“…Foxy grapes, on the other hand, known as Vitis labrusca, are valued for their distinctive foxy flavor and are used extensively in the production of grape juice, jams, and jellies [5]. They have gained attention for their potential health benefits such as antioxidant properties [6]. Table grapes, namely the 'Italia' and 'Bronx Seedless' cultivars, have gained prominence not only for their exquisite taste [7], but also for their abundant phytochemical content, which encompasses phenolic acids, C 13 -Norisoprenoids; phytoalexins, and flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental changes have been reported to affect the uptake of mineral elements by plants and to alter the synthesis of different classes of hormones in plants, which in turn affects plant growth ( Ulger et al., 2004 ). Keskin et al. (2022) found that indole-3-acetic acid, salicylic acid, cytokinin, and zeatin contents in plants were significantly and positively correlated with the contents of P, Mn, Ca, S, K, and Mg, as well as the activities of catalase, peroxidase, and superoxide dismutase, and significantly and negatively correlated with abscisic acid content.…”
Section: Resultsmentioning
confidence: 93%
“…Effect of pretreatment chemicals namely, oak ash and potassium carbonate on the hormones and some other nutrients like minerals, vitamins, and also on antioxidants have been examined and findings revealed that application of oak ash as pretreatment promoted the content of hormones and other nutritional components of raisins compared to potassium carbonate treatment (Keskin et al, 2022).…”
Section: Pretreatment Of Grapementioning
confidence: 99%